Tectonic Clash: An Interactive Game-Based Learning Intervention for Mastering Earth Science Concepts - Aludos, Allen Van B.; Tultog, Ashley A.; Naggoc, Zyrene Joy P.; Guinid, Juana A.; Pasigon, Christzon P. (Journal of Educational Research and Practice, 2025)
This study investigates the effectiveness and acceptability of Tectonic Clash, a game-based learning intervention designed to improve science students' mastery of earth science concepts. In response to persistent challenges in Earth Science education in the Philippines, as evidenced by low international assessment scores, the study aims to explore innovative teaching strategies that enhance student engagement and concept mastery. The card game was evaluated by fifty pre-service and ten teachers using an evaluation form. Findings show that the game has the potential to stimulate critical discussion and encourage deeper engagement with scientific content. Both teacher groups rated the game highly across dimensions, including rules, design, color/graphics, fonts, artwork, and conceptual accuracy. Mean scores across all categories ranged from 4.23 to 4.9, indicating strong agreement on the game's educational value and design quality. The results confirm that Tectonic Clash effectively reinforces key Earth Science concepts and is well-received as a pedagogical tool. The study demonstrates the potential of game-based Learning to address persistent educational gaps and foster long-term retention in science education.